Developing Module for Ethnic Interaction in Secondary School in Malaysia - Dawi, Amir Hasan; Mahizer Hamzah; Noraini Mohamed Noh; Norazilawati Abdullah; Norwaliza Abdul Wahab (European Journal of Social Science Education and Research, 2018)
This paper is on developing the module for interethnic interaction in Malaysian secondary schools. The research found that students in Malaysian secondary schools have some difficulties to interact with other students from different ethnic groups. This mainly because they had attended different types of schools and culture in primary level. The formal education has separated them by the type of schools. They also practice daily activities within their own culture. Both factors have formed and strengthened their habitus of ethnicity. Hence there is a need to overcome the interethnic interaction issue in secondary schools. A research was carried out to identify the important aspects of Malaysia culture that should be understood by all students. Interview and observation were carried out to gain data from participants. The interaction module was designed accordingly with the themes. The presentation will conclude the themes that considered to be covered in the module.